The effect of nauplii Artemia sp. enriched with biofloc on the performance of Penaeus monodon and Penaeus vannamei post-larvae - Supono Supono; Ayu N Yanti; Anggita P Pertiwi; Tarsim Tarsim; Wardiyanto Wardiyanto (Syiah Kuala University, 2020)
Artemia sp. is a common natural feed for shrimps at the post-larvae stage and is characterized by poor lipid content. Therefore, Artemia is commonly enriched with specific nutrition, including biofloc. This contains some useful nutrients in the form of protein and polyhydroxy butyrate (PHB). The aim of this study was to analyze the effect of Artemia enriched with biofloc on the growth performance of black tiger shrimp, P. Monodon, and whiteleg shrimp P. vannamei. This research used acompletely randomized design (CRD), encompassing three treatments of feed and four replications. The tested treatments include: (a) Artemia sp. without enriched (b) Artemia enriched with biofloc, and (c) biofloc without Artemia, and the treatments were fed on black tiger as well as whiteleg shrimp post-larvae for 15 days. The results showed the significant effect of using Artemia sp. enriched with biofloc on the growth of P. monodon and P. vannamei, but not on the survival rate. However, both parameters were significantly influenced for post-larvae shrimp at a dose of 30 mL biofloc. This served as a nutritional source by providing the best growth of 14.57 mg and 15 mg at a daily growth and survival rate of 0.86 mg day-1: 98% and 1.4 mg day-1: 99% for P. vannamei and P. monodon, respectively.